Forever Seeing New Beauties : The Forgotten Impressionist Mary Rogers Williams, 1857−1907 - Kahn, Eve M. (Book collections on Project MUSE., 2019)
"Mary Rogers Williams was born and raised in Hartford, Connecticut. She taught art at Smith College and travelled extensively through Europe and Scandinavia. Her work was shown in New York, Boston, and Paris; critics of the day didn't know what to make of her "poetic sensibility" and "shadowy quality". The book includes color reproductions and illustrations. About the author: Eve M. Kahn is a freelance writer specializing in architecture, design and preservation, and was Antiques Columnist at The New York Times, 2008-2016"--